The Title Should Be Concise, Informative And Clear, Allowed To Include A Subtitle Academic Supervision Management Of School Principles To Improve Professional Competence Aliyah Madrasah Teacher In Bandung Regency (Case Study On Ma Ar-Rosyidiyah And Ma Al- - Nur Asyiah; Ade Tutty R Rosa; Hanafiah; Supyan Sauri (IJGIE (International Journal of Graduate of Islamic Education), 2022)
The general objective of this study is to identify and describe the academic supervision of the principal to improve the professional competence of Madrasah aliyah teachers in Bandung Regency. This study uses a qualitative approach and descriptive method. Collecting data using interviews, study documentation and observation. The results showed that the planning was prepared referring to the identification of problems faced by teachers based on the results of the previous year's supervision such as assessment, coaching, assisting teacher difficulties, and SWOT analysis, then poured into the Academic Supervision Plan (RKA) program according to the needs of the teacher; Organizing is regulated and allocated among stakeholders so that organizational goals can be achieved effectively, as well as the principal's work program plan through the RKA and RKM in the annual program. Academic supervision by the principal is carried out in three stages, namely: an initial survey before conducting academic supervision, class visits, reviews and solutions. Evaluation, including job descriptions and documentary evidence. Evaluation is carried out at the end of each semester. In improving the competence of teachers, principals also found several obstacles in the field, an effort to solve the inhibiting factors is to organize training based on the needs of the teachers. Guidance through teacher training to improve the competence of principal teachers also found several obstacles in the field, the solution effort was to organize training based on the needs of teachers.